Evolusi Pesantren Pondok Pesantren Qomaruddin Sampurnan Bungah Gresik: Dari Akar Tradisional Menuju Modern - Fatih Ahmad, Nur; Inayatul Mahfudloh, Ririn; Nur Faizah (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Pesantren Qomaruddin Sampurnan Bungah Gresik, as one of the oldest Islamic educational institutions in Indonesia, has undergone a long journey in its transformation from a traditional educational system to a more modern and multidisciplinary approach. Initially, this pesantren focused on teaching classical Islamic texts (kitab kuning) using the *sorogan* and *bandongan* methods. However, over time, due to social changes and the development of knowledge, Pesantren Qomaruddin began adopting a more diverse curriculum, including general subjects such as science, technology, and foreign languages. This modernization also includes updates in teaching methods, the use of information technology, and collaboration with formal educational institutions. This article examines the evolution process, highlighting the driving factors behind the changes, the challenges faced, and its impact on the pesantren community and the surrounding society. Thus, Pesantren Qomaruddin becomes a concrete example of how traditional educational institutions can adapt and remain relevant in the globalization era without losing their Islamic identity.